AB0297 Real-Life Effectiveness of Golimumab in Biologic-Naïve Rheumatoid Arthritis Patients – Data from reuma.pt, A Portuguese Registry. (15th July 2016) - Mourão, A.F.; Ribeiro, C.; Borges, J.; Gonçalves, M.J.; Bernardes, M.; Fernandes, S.; Dezerto, R.; Laires, P.A.; Machado, P.; Eusébio, M.; Santos, M.J.; Canhão, H.; et al.
Abstract : Background: Registries are becoming an increasingly important source of data, providing additional information on the use of biologics in clinical practice. The real-world clinical data currently available regarding the use of SC anti-TNFs is still limited. Therefore, it is of utmost importance to increase the knowledge of Golimumab (GLM) effectiveness in the clinical practice. Objectives: This study was designed to access the effectiveness of SC GLM 50 mg/monthly + MTX through 52 weeks of treatment in biologic-naïve RA patients. The primary objective was to investigate the proportion of patients achieving clinical remission (DAS28ESR<2.6). The secondary objectives were the evaluation of: the treatment persistence rates; the proportion of patients achieving functional response (ΔHAQ>0.22); and the effect of treatment on DAS28 individual components. Methods: This was a retrospective non-interventional study based on the Rheumatic Diseases Portuguese Register (Reuma.pt). It was conducted in a cohort of patients aged >18 years with active RA despite previous treatment with conventional DMARDs, biologic-naïve, who started SC GLM+MTX, from March 2011 to August 2015. The cumulative incidence of achieving clinical remission, treatment persistence and functional response/remission were estimated using survival analysis. Cox regression was used to calculate the hazard ratios. Results: A total of 109 patients (86.3% female, mean age 55.5±13.2 years; mean age of diagnosis 45.5±13.5 years, rheumatoid factor 78% positive) met the study criteria. Ninety-three had a follow up of at least 52 weeks (i.e. all patients who started treatment before August 2014). At week 52, 38.3% of patients were on clinical remission, 91.9% achieved functional response and 35.2% were on functional remission (HAQ<0.5). The treatment persistence rate was 75.3% for the individuals who were in the study for ≥52 weeks (Figure 1 ). For functional remission, high CRP levels at baseline seem to be a determining factor (HR=0.54, p =0.026). Conclusions: This is the first Golimumab data analysis generated from the Portuguese registry Reuma.pt. Our results are in agreement with data from other national registries and demonstrate the long-term effectiveness and the high treatment persistence rates of GLM through 52 weeks. Disclosure of Interest: A. F. Mourão Consultant for: Merck Sharp & Dohme, C. Ribeiro: None declared, J. Borges: None declared, M. J. Gonçalves: None declared, M. Bernardes: None declared, S. Fernandes: None declared, R. Dezerto Employee of: Merck Sharp & Dohme, P. A. Laires Employee of: Merck Sharp & Dohme, P. Machado Employee of: Merck Sharp & Dohme, M. Eusébio: None declared, M. J. Santos: None declared, H. Canhão: None declared